The effects of transdermal testosterone and oestrogen therapy on dry eye in postmenopausal women: a randomised, placebo-controlled, pilot study - Golebiowski B, Blanka; Badarudin, Noor Ezailina; Eden, John; Gerrand, Leanne; Robinson, Jennifer; Liu, Jinzhu; Hampel, Ulrike; You, Jingjing; Stapleton, Fiona (BMJ, 2016)
Aims Sex hormones could provide a future treatment avenue for dry eye post menopause. However, there are few well-controlled studies. This study investigates the impact of testosterone and oestrogen on dry eye symptoms and signs in postmenopausal women. Methods A randomised double-blind placebocontrolled pilot study was conducted involving 40 women with dry eye (age 63.9±5.1 years, 13.2 ±6.3 years post menopause). Ten women were assigned to each of four treatment groups: transdermal testosterone, oestradiol, testosterone/oestradiol combination and placebo. Assessment at baseline and after 8 weeks: ocular symptoms, tear osmolarity, tear stability, tear secretion, meibomian gland assessment, corneal and conjunctival sensitivity, serum concentrations of 17β-oestradiol, 3-α-androstanediol-glucuronide and dehydroepiandrosterone sulfate. Differences from placebo were examined using one-way analysis of variance and Dunnett’s t-test. Within-group analyses included paired t-tests and Spearman correlation. Results Dryness intensity after 8 weeks was significantly worse in the oestrogen group compared with placebo (p=0.04). No significant changes in other symptoms, tear function, meibomian gland function, lid morphology, corneal or conjunctival sensitivity were observed in any of the groups when compared with the change in placebo after 8 weeks. Within-group analyses showed increased tear secretion in the testosterone/ oestradiol combination group ( p=0.03) and a strong association between increased serum androgen and improved tear stability in the testosterone group (ρ=0.83,p=0.01). Conclusions Oestrogen supplementation may worsen ocular symptoms in postmenopausal women with dry eye, whereas no impact of testosterone therapy on symptoms was apparent. The positive effects of oestrogen and testosterone on tear function require confirmation in a larger study, with sample size calculated from the data generated herein. Placebo control is essential in studies of dry eye therapies.